2014
DOI: 10.1155/2014/247384
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Parameter Identification of the Vibration Characteristics of Armature Assembly in a Torque Motor of Hydraulic Servo Valves under Electromagnetic Excitations

Abstract: The resonance of the armature assembly is the main problem leading to the fatigue of the spring pipe in a torque motor of hydraulic servo valves, which can cause the failure of servo valves. To predict the vibration characteristics of the armature assembly, this paper focuses on the mathematical modeling of the vibration characteristics of armature assembly in a hydraulic servo valve and the identification of parameters in the models. To build models more accurately, the effect of the magnetic spring is taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Integrating each of the component transfer functions (8), (10), (12), and (13), we can acquire the transfer function structure diagram of the whole hydraulic flexible towing speed control system which is shown; the transfer function diagram of the underwater vehicle speed control system may be obtained in Figure 4.…”
Section: Modeling Of the Underwater Vehicle Speed Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating each of the component transfer functions (8), (10), (12), and (13), we can acquire the transfer function structure diagram of the whole hydraulic flexible towing speed control system which is shown; the transfer function diagram of the underwater vehicle speed control system may be obtained in Figure 4.…”
Section: Modeling Of the Underwater Vehicle Speed Control Systemmentioning
confidence: 99%
“…In modern times, many scholars have done plenty of research work on the modeling of hydraulic and fluid systems with rope actuation [5,6] and proposed a good deal of advanced control technology such as feedback, neural network, adaptive robust control, and predictive control [7][8][9][10][11]. In order to predict the vibration characteristics of the armature assembly, Peng et al focused on the mathematical modeling of the vibration characteristics of armature assembly in a hydraulic servo valve and the identification of parameters in the models [12]. Chen et al developed the dynamic model of the valve-controlled hydraulic winch by linearizing its nonlinear dynamics at an operating point and found that the FUZZY P + ID controller is much more robust than the conventional PID controller [13].…”
Section: Introductionmentioning
confidence: 99%
“…Kawashima et al [15] analyzed how using a slit structure instead of an orifice plate could reduce the pressure fluctuation by 75% and the noise level approximately by 15 dB in the flapper-nozzle type servo-valve. Peng et al [4,16] also studied how the pressure pulsations could induce resonance excitation in the flapper-nozzle valve. They indicated that self-excited oscillation of the flapper-armature generated by the fluid-structure interaction can cause the self-excited noise and squeal noise.…”
Section: Introductionmentioning
confidence: 99%
“…The results show the large magnitude of vibration for a low damping ratio of that frequency. 20 Somashekhar et al 21 developed a mathematical model of a jetpipe servovalve with a built-in mechanical feedback. The FEM approach was employed to determine the stiffness of the critical components of the feedback spring and jetpipe assembly.…”
Section: Introductionmentioning
confidence: 99%